Pelatihan Pengembangan Strategi Pemasaran Jamur Tiram Putih Desa Ngijo Kecamatan Tasikmadu Kabupaten Karanganyar - Sriyanto Sriyanto; Fadjar Harimurti (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Pokoh Hamlet, Ngijo Village, Tasikmadu District, Karanganyar has various potentials, one of which is the cultivation of white oyster mushrooms. The main constraints on the marketing aspect and the tight competition of oyster mushroom craftsmen. The PKM team intends to help Partners provide marketing strategy development training. With this training, partners are expected to have better marketing skills. The PkM activity was held on Saturday 25 March 2023 with the aim of providing training in developing marketing strategies. This training activity received a positive response from Partners. From the results of the question and answer, Partners have understood the material related to marketing strategy development. The results of this training are expected to be a provision for Partners in developing their business and making a major contribution to sales and profits.